Jordanian telecommunication companies success through human capital and social capital - Rashidah, Mohamad Ibrahim; Abdul Malek, A. Tambi; MumenYasinMoshalesh, Al Dalaien (2020)
Nowadays, organizational success is dominantly variable that posits vast chances and defiances to the decision making and staff of telecommunications. This current study aimed to uncover the effect of human and social capital on organization success in Jordan. The data proportionally collected from 234 managers of Telecommunication companies. This study used PLS-SEM.3 software in analyzing the data. The results concluded that human capital had a positive impact on organization success; however, the norms of social capital had a positive impact on organization success. The managerial implications indicated from results that the managers in telecommunications companies that the social capital has a substantial impact on organization success. Therefore, they need to fetch fundamental changes in human and social capital for comprehensive development and organization success in Jordan.